MODELING OF INTERACTION BETWEEN AN INVESTOR AND A TRUST MANAGER WITH NONLINEAR FUNCTIONS - S. V. Korzhnev (Вестник университета)
The article is devoted to studying interaction between investor and trust manager. There is an information asymmetry between the investor and the trust manager, which makes it necessary to create a model that would allow the investor to overcome this asymmetry at least partially and get information about the quality of the service. In previous researches, the author proposed a theoretical model, describing this interaction with linear functions. In this paper, a model with nonlinear functions has been created and the conclusions of the linear and the nonlinear models have been compared. As a result, the conclusions of models with linear and nonlinear functions regarding the nature of the relationship between the commission and the factors used in the model were the same.